Analytical and numerical analysis of functionally graded (FGM) axisymmetric cylinders under thermo-mechanical loadings. (December 2022) - Das, P.; Islam, M.A.; Somadder, S.; Hasib, M.A.
Abstract: This study examines the thermo-mechanical behavior of FGM hollow cylinders subjected to mechanical loading and steady thermal stresses. The distribution of temperature, displacement, and stresses on the cylinder's inside and outside surfaces is considered a function of radius. The analytic solution of the displacement and stress distributions was obtained by solving Navier's second-order differential equation using the integral and differential transform method, derived from the mechanical equilibrium and heat equations. Moreover, numerical models were built using the finite element method with USDFLD and the finite difference method to test the accuracy of the analytical solution. The analytical formulation and numerical simulation predictions have a high level of agreement, indicating that the model is accurate. The effect of inhomogeneity in the FGM thick cylinder was addressed in this study by selecting a non-dimensional parameter β = [ − 2, 2 ] that may be assigned any value influencing the stresses in the cylinder. It is concluded that by altering the value β, the properties of FGM can be altered to achieve the lowest stress levels. It is also shown that the effect of various Boundary Conditions (B.Cs) is significant in stress fields. This present work also observed that the significance of thermal B.C. is more dominant than fixed pressure B.Cs. Graphical Abstract: ga1